Effect of Auditory Integration Training on Children with Autism Spectrum Disorder and Auditory Attention Disorder - HUANG Qijun; ZHOU Kun; LIU Zhenhuan; YANG Jie (康复学报)
ObjectiveTo observe the effect of auditory integration training on language, social communication and behavior of Children with autism spectrum disorder (ASD) and auditory attention disorder.MethodsA total of 83 ASD children with auditory attention disorder treated in the children rehabilitation department of Changsha Maternal and Child Health Hospital from January 2020 to May 2021 were randomly divided into control group and observation group, with 41 cases and 42 cases respectively. The control group received comprehensive rehabilitation training including the language training, behavior therapy, sentiment training and brain bionic electrical stimulation, once a day, five times a week, 20 times for a course of treatment in one month, with a rest interval of 3-5 days, lasting for nine months. In addition to the treatment of the control group, the observation group received auditory integration training for 30 minutes a time, once a day, 20 times for a course of treatment in one month, with a rest interval of two months, lasting for nine months. Before and after treatment, the missing number method was used to evaluate the auditory attention Gesell child development scale was used to evaluate the language and social communication skills; Psycho educational profile-3 (PEP-3) was used to evaluate the communication and behavior skills; Childhood autism rating scale (CARS) and autism behavior checklist (ABC) were used to evaluate the typical symptoms of autism.Results1) Auditory attention: compared with that before treatment, the scores of the auditory attention of both groups significantly increased after treatment (P<0.05). The observation group scored higher in the auditory attention than the control group after treatment (P<0.05). 2) Language and social communication skills: compared with that before treatment, the scores of language and social communication skills in Gesell scale of both groups significantly increased after treatment (P<0.05). Compared with the control group, the scores of language and social communication skills of the observation group after treatment were statistically higher (P<0.05). 3) Communication and behavior skills: compared with those before treatment, the scores of communication and behavior skills of PEP-3 scale of both groups significantly increased after treatment (P<0.05). The scores of communication and behavior skills of PEP-3 scale of the observation group were statistically higher than those of the control group after treatment (P<0.05). 4) Typical symptoms of autism: compared with those before treatment, the scores of ABC and CARS of the observation group after treatment decreased significantly (P<0.05). Compared with the control group, the ABC and CARS scores of the observation group after treatment were statistically lower (P<0.05).ConclusionAuditory integration training can effectively improve the auditory attention, language, social communication, communication and behavior skills of acoustic children with auditory attention disorder, and alleviate the typical symptoms of autism.